2003
DOI: 10.1007/s00134-003-1767-2
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors of nosocomial catheter-associated urinary tract infection in a polyvalent intensive care unit

Abstract: In our study, the drainage system did not influence the occurrence of bacteriuria. To decrease the rate of catheter-associated bacteriuria in polyvalent ICU patients, removal of the bladder catheter must be performed as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
17

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 15 publications
3
37
0
17
Order By: Relevance
“…1,5,6,8,15 Strategies to decrease the duration of catheterization have been recommended, such as reminding physicians to review whether a catheter is still appropriate and using automatic stop orders to facilitate the removal of catheters when the devices are no longer needed. 8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate.…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
“…1,5,6,8,15 Strategies to decrease the duration of catheterization have been recommended, such as reminding physicians to review whether a catheter is still appropriate and using automatic stop orders to facilitate the removal of catheters when the devices are no longer needed. 8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate.…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
“…Apesar de a literatura mencionar o sexo feminino como fator de risco para ocorrência de ITU [11][12][13] , houve mais incidência entre os pacientes do sexo masculino. No entanto, essa diferença não foi estatisticamente significativa (p = 0,35; IC 95% [0,64-3,38]).…”
Section: Discussionunclassified
“…[22,25] Yoğun bakımda tedavi alan hastalarda yapılan bir çalışmada kadın cinsiyeti kateter ilişkili idrar yolu enfeksiyonu gelişimi için bağımsız bir risk faktörü olarak bulmuşlardır. [26,27] Çeşitli hasta grupları üzerinde yapılan çalış-malarda kadın cinsiyet ile kateter ilişkili idrar yolu enfeksiyonu gelişimi arasındaki ilişkiyi gösterilmiştir. [28,29] Bizim çalışmamız-da tek değişkenli analizde kadın cinsiyet ile kateter ilişkili idrar yolu enfeksiyonu arasında anlamlı korelasyon saptandı.…”
Section: Discussionunclassified